How to Combine SHJ Cell-Edge Passivation and Module Reliability? - Samuel Harrison; Mickael Albaric; Vincent Barth; Benoit Martel; Marco Galiazzo; Nicola Frasson; Agata Lachowicz (SiliconPV Conference Proceedings)
The use of cut-cells in most of the current modules is now the norm to maximise the final product performances. But the integration of such new cell configurations also comes with new challenges, especially if small cell size dimensions such as shingle are considered. Indeed, specific edge passivation processes are often used to recover for the cut-cell losses. Alumina Oxide or Polymer deposition are the most studied approaches, with in general promising benefits proven at cell level. However, only few communications after module integration are available, in particular about the impact of these additional layers on final module reliability. We show for example that it is crucial to avoid direct deposition of AlOX over the cell metal pattern in the future interconnection area, as TC (Thermal Cycling) resilience of such modules is clearly degraded. Proper edge localization of the AlOX layer is needed to recover the initial reliability behaviour. To preserve the interconnection quality, three different approaches are investigated: (1) edge localisation of the layer by wafer stacking during deposition (2) introduction of adapted copper plating solutions allowing metal growth through the passivation layer (3) edge passivation process directly applied on final strings just before lamination.